Accountancy for banking students - Edwards, J. R.; Mellet, H. J. (London : Chartered Institute of Bankers, 1994)
Written to meet the needs of bankers and, more specifically, to help banking students prepare for and pass the accountancy paper in the Chartered Institute of Bankers' Associateship examinations.
Includes index..
oif 30/01/15
Loan
Keywords: Accounting; Banks and banking; Accountancy